Green synthesis, characterization and sorption efficiency of MnO2 nanoparticles and MnO2@waste eggshell nanocomposite. Issue 1 (31st December 2022) - Moeen, Mariya; Nouren, Shazia; Zaib, Maria; Bibi, Ismat; Kausar, Abida; Sultan, Misbah
ABSTRACT: This study reported the biological synthesis of MnO2 nanoparticles and MnO2 @eggshell nanocomposite. Optimum conditions for the biosynthesis of MnO2 NPs were observed for 0.025 M MnCl2 solution with 1.0% (m/v) of plant powder (Ocimum basilicum) content-based extract under basic pH conditions. Afterwards, nanocomposite (NC) was prepared by fabricating manganese-based nanoparticles on waste eggshell powder. Different techniques were applied for characterization of prepared materials. Synthesized NPs and NCs were further utilized for the adsorption studies of crystal violet dye. Studies were conducted to delineate the effect of dye concentration, prepared material dosage, pH, temperature and contact time. In the end, adsorption isotherms and thermodynamic studies were applied to the data. The Langmuir model better fits the data in both the cases and predicted adsorption capacity of 149.254 and 52.6 mg/g for NC and NPs, respectively. The possible mechanism of the dye removal process, nanoparticle and nanocomposite formation has also been discussed. GRAPHICAL ABSTRACT: UF0001